Can immature reticulocyte fraction be an inflammatory biomarker in late-preterm infants diagnosed with congenital pneumonia? (Annals of Medical Research, 2021)
Aim: Congenital pneumonia (CP) is serious respiratory infection of the neonates. Recently introduced hematological parameter, immature reticulocyte fraction (IRF), has been investigated to gather clinical information about the prognosis of anemia as well as to measure the level of inflammatory activity in adult patients. In this study of late-preterm infants diagnosed with CP, we compared IRF with common sepsis biomarkers and evaluated its role as inflammatory biomarker in neonates.Material and Methods: Late-preterms were categorized based on infectious vs. non-infectious etiology of the respiratory distress. Blood samples were taken at 48-72 hours after birth. IRF was measured with Sysmex XN-3000. Biomarkers such as complete blood count parameters, C-reactive protein (CRP), and procalcitonin (PCT) were used for the comparison. Results: Total of 25 late-preterms, 14 in CP-group and 11 in transient tachypnea of the newborn (TTN) group were included study. The groups were comparable in terms of gestational age, birth weight and cesarean section rate. The proportion of prolonged membrane rupture was significantly higher in CP-group. No significant differences were found between hemoglobin, hematocrit and reticulocyte in both groups (p>0.05). The value of IRF was higher in CP-group compared to in TTN-group, although it was not statistically significant (37.8±7.2% vs. 31.6±9.4%, respectively) (p=0.08). PCT was significantly higher in CP-group (p=0.017). No differences were found in other biomarkers between the groups (p>0.05). Conclusion: Our results suggest that PCT can be diagnostic marker in CP, but further studies are needed to confirm role of IRF in neonatal inflammation.Conclusion: Among patients presenting to the ED with STEMI, a high lactate level is associated with mortality. Also, the difference between lactate values of the patients after PTCA is associated with the risk of mortality. Therefore, we consider that first lactate levels in ED and last lactate levels after PTCA in patients with STEMI can provide physicians with an insight into the possibility of mortality.
Keywords: Biomarker; immature reticulocyte fraction; neonate